PREFERENSI KONSUMEN PERUMAHAN BERDASARKAN UNDANGUNDANG NOMOR 1 TAHUN 2011 TENTANG PERUMAHAN DAN KAWASAN PERMUKIMAN DI WILAYAH KOTA SENTANI - Aditya Yudy Anggoro; Dewi Ana Rusim; Harmonis Rante (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
There needs to be a thorough understanding of what are the preferences of residential consumers, where there is a choice of likes or dislikes, feelings of pleasure, satisfaction, and comfort towards something that is the choice of housing consumers so that satisfaction and comfort can be fully fulfilled, not forced to be satisfied because they make the best choice. from the worst. The objectives to be achieved in this study are to analyze the completeness of infrastructure, facilities, and public utilities, analyze the availability of infrastructure, facilities, and public utilities based on the preferences of residents as consumers, analyze the basic factors for assessing the availability of infrastructure, facilities, and public utilities based on residents' expectations. To achieve the objectives in this study, it was carried out using a quantitative research approach with factor analysis. From the analysis of the data obtained for the availability of Infrastructure, Facilities and Utilities, not all requirements can be met such as Road Infrastructure, Drainage and Availability of Trash Cans. There is a prayer room in Marwah Indah Housing and green open space in the form of fishing ponds, parks, entertainment facilities for other children's games are located at Joko Indah Housing. For utilities, the electricity network and telephone network are available in all three housing estates. Elements of infrastructure, facilities and utilities as well as Elements of Ease of Accomplishing Activities generally gave an agreeable answer that these elements became consumers' preferences in choosing and determining housing, but the element of availability of supporting facilities respondents gave neutral/undecided/less answers. Characteristics of Housing Development based on the answers given by respondents summarized 9 main factors that became the basis for assessment as housing consumers